Postoperative cerebrovascular complications in high-risk patients with coronary artery disease in cardiac surgery - Gogayeva, Olena K.; Rudenko, Anatolii V.; Lazoryshynets, Vasyl V. (Ukrainian Neurosurgical Journal, 2021)
Aim: to analyze the frequency and specificity of cerebrovascular complications in patients with coronary artery disease (CAD) after cardiac surgery. Materials and methods: a retrospective analysis of data of 354 randomly selected patients with CAD who were operated on and discharged from the Amosov National Institute of Cardiovascular Surgery, Ukraine from 2009 to 2019. The average age of the patients was 61.9±9.6 years old. In preoperative risk stratification according to the EuroSCORE II scale, patients were classified as high cardiac risk, the predictive risk of death was on average 8.8%. All patients underwent general clinical examinations, ECG, ECHO, coronary angiography and surgical treatment of CAD. Duplex scanningf the brachiocephalic arteries (BCA) was performed in 280 (79.09%) patients. Results: 43 (12.1%) patients had a history of stroke. Among 280 patients who underwent ultrasound examination of BCA, stenosis more than 50% of the internal carotid arteries was diagnosed in 95 (33.9%) cases. For hemodynamically significant (> 70%) BCA stenoses, hemodynamic stability and coronary artery lesions that didn’t require emergency surgery, a neurosurgeon’s consultation is required. The predictive risk of postoperative stroke on the STS scale in average was 1.48±0.98% [range 0.2–6.8%]. In the postoperative period, in 10 (2.8%) patients non-fatal cerebrovascular accidents were developed, among which 5 (1.4%) had an ischemic stroke, and 5 (1.4%) had a transient ischemic attack. The risk of neurological complications in the perioperative period increases in patients with a history of stroke (р = 0,0002), preoperative atrial fibrillation (р = 0,013), aortic calcification (р = 0,003) and more significant decrease of blood pressure on the 1st postoperative day (systolic pressure p = 0.005, diastolic pressure p = 0.0008). Conclusions: strict monitoring of blood pressure and prevention of hypotension are required at all stages of patients management. The cardiac surgeon, whenever possible, limits manipulations on the atheromatous aorta, using the no-touch aorta technique, by performing total arterial revascularization. The work of a multidisciplinary team helps to avoid life-threatening events.